Images from the GOES 8 satellite and their applications in meteorology - Del Carpio, Jorge A. (2003)
This work describes the prosecution of the images of the satellite GOES 8 to be used in applications in Meteorology, such as locating the nubosidad conditions and ofprecipitation, observation of the conditions of clear sky, observation of the area of convergence intertropical (ZCIT) and other meteorological processes to regional scale. Likewise the results of the prosecution will be shown using the Matlab Version 6.0. they will also be explained other advantages of the presented method. recursos hidráulicos.